ASSESSING THE IMPACT OF JUST-IN-TIME LOGISTICS ON EFFECTIVE INVENTORY MANAGEMENT IN CONSTRUCTION PROJECTS IN THE SOUTH-SOUTH REGION OF NIGERIA - Glory Williams Archibong; Kelechi Enyinna Ugwu; Erasmus Ejike Duru (American Journals, 2025)
The construction industry in Nigeria’s South-South region faces significant challenges in material management, leading to inefficiencies, cost overruns, and delays in project delivery. This study investigates the impact of Just-in-Time (JIT) logistics on effective inventory management in selected construction projects within this region, focusing on the interplay between inventory control and JIT implementation. Utilizing a correlational research design, data were collected from 208 respondents across top, middle, and lower management levels using a validated questionnaire based on a five-point Likert scale. Statistical analysis, including regression and ANOVA, revealed a strong negative correlation (R = 0.751, R Square = 0.564) between JIT logistics and inventory levels, rejecting the null hypothesis that JIT does not affect inventory levels (p = 0.000). Survey results indicated high agreement (88.94%–98.08%) on the importance of inventory management practices, such as real-time tracking and optimal inventory levels, in supporting JIT’s goals of waste reduction and timely material delivery. Major challenges identified include complex return processes (93.27% agreement) and lack of coordination (97.60% agreement), which hinder JIT effectiveness. Proposed strategies to optimize construction efficiency include adopting advanced tracking systems, streamlining return processes, enhancing supplier coordination, implementing lean principles, and providing staff training.
Keywords: Construction Efficiency, Just-in-Time (JIT) Logistics, Lean Construction, Inventory Management, Material Management